2000
DOI: 10.1053/jhep.2000.19796
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Carboplatin–Coated Tube for the Unresectable Cholangiocarcinoma

Abstract: Most cases of cholangiocarcinoma have reached an unresectable stage by the time they are discovered despite significant progress of diagnostic modalities. Many of these patients with obstructive jaundice are often treated by biliary drainage using stents to relieve the jaundice. However, the stent patency period is as short as 3 to 9 months because of tumor ingrowth or overgrowth, and mean survival is at most 12 months. Therefore, both continuous relief of obstructive jaundice and local control of the tumor ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Biliary stent placement combined with local tumor therapy, such as brachytherapy, extra-radiation therapy, or arterial infusion chemotherapy, can prolong the survival time of patients with malignant biliary obstruction [65][66][67][68] . Mezawa et al [69] developed a new PTBD tube coated with carboplatin.…”
Section: Palliative Therapymentioning
confidence: 99%
“…Biliary stent placement combined with local tumor therapy, such as brachytherapy, extra-radiation therapy, or arterial infusion chemotherapy, can prolong the survival time of patients with malignant biliary obstruction [65][66][67][68] . Mezawa et al [69] developed a new PTBD tube coated with carboplatin.…”
Section: Palliative Therapymentioning
confidence: 99%
“…Another relatively recent and novel approach to palliation of unresectable cholangiocarcinoma involves the use of carboplatin-impregnated plastic biliary stents as a means of delivering cytotoxic chemotherapy directly to the tumor tissue. 10 This approach is interesting, but it also is limited by the fact that it is only effective against local and not disseminated tumor. Last, liver transplantation is not generally indicated for cholangiocarcinoma, in large part because of the high tumor recurrence rates, although a small, selected group of patients with early-stage disease have benefited from this procedure.…”
mentioning
confidence: 99%
“…36 In vitro and in vivo studies (the latter using drug-coated SEMSs) have demonstrated that local exposure to paclitaxel, 5-fluorouracil, and gemcitabine can induce local responses when placed in contact with both benign and malignant GI tract tissues. [37][38][39][40][41][42][43][44] To date, there are only a few small published case series in humans. These demonstrated that partial responses in unresectable cholangiocarcinoma can be achieved with a carboplatincoated percutaneous biliary tube, 45 and endoscopically placed drug-eluting SEMS may be associated with improved stent patency and overall survival in patients with extrahepatic cholangiocarcinoma.…”
Section: Drug-eluting Stents In the Gi Tractmentioning
confidence: 99%